A concurrent multiscale framework based on self-consistent clustering analysis for cylinder structure under uniaxial loading condition. (15th June 2021) - Feng, Yixin; Yong, Huadong; Zhou, Youhe
Abstract: Accurate and efficient multiscale simulation of multifilament composite remains challenges due to expensive computation cost of solving the nonlinear representative volume element (RVE) responses in microscale. An effective reduced-order method called self-consistent clustering analysis (SCA) has been proposed recently to solve the dilemma. This paper extends the application of traditional multilevel finite element (FE 2 ) to cylinder structure with domain division, where the inner domain is computed by finite element method (FEM) with SCA instead of direct FE 2 method and outer domain is calculated by conventional FEM. The presented framework is named as concurrent modified FEM-SCA. To validate the accuracy and efficiency of presented method, the computation results of SCA, Fast Fourier Transform (FFT) and FEM are compared in microscale at first. Then, under the presented framework, the cylinder structures with diverse RVEs in uniaxial loading are studied, and the results are compared with full-scale direct numerical simulation (DNS) by FEM. Besides, the effects of different element positions, inclusion variations and loading phases on the RVE responses are also studied.